1998
DOI: 10.1095/biolreprod59.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Adult Leydig Cells in the Neonatal Rat Testis Is Arrested by Hypothyroidism1

Abstract: The effects of propyl thiouracil (PTU)-induced hypothyroidism on testicular interstitial cells and androgen secretion in vitro in the neonatal rat were investigated using Sprague Dawley rats of 1, 7, 14, and 21 days. The results revealed that the fetal Leydig cell (FLC) number per testis was unchanged between and within treatment groups at all ages tested. FLC size was 50% smaller in 21-day controls than in all other groups. Adult Leydig cells (ALCs) were present at Days 14 and 21 in controls but were absent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
76
7
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 29 publications
17
76
7
1
Order By: Relevance
“…It was previously reported that FLCs decline in number after birth, a cellular process suggested to be associated with: (a) cell death (Kuopio et al, 1989), (b) dedifferentiation to fibroblastictype cells (Gondos et al, 1974) or (c) transformation to adult-type Leydig cell population (Mendis-Handagama et al, 1998). However, several studies suggested that PFLCs do not all enter apoptosis and degenerate but can persist in later puberty (Kerr and Knell, 1988;Ariyaratne and Chamindrani Mendis-Handagama, 2000;Ivell et al, 2003).…”
Section: Effect Of (Bu) 2 Camp and Paracrine Factors On Pflc Prolifermentioning
confidence: 99%
“…It was previously reported that FLCs decline in number after birth, a cellular process suggested to be associated with: (a) cell death (Kuopio et al, 1989), (b) dedifferentiation to fibroblastictype cells (Gondos et al, 1974) or (c) transformation to adult-type Leydig cell population (Mendis-Handagama et al, 1998). However, several studies suggested that PFLCs do not all enter apoptosis and degenerate but can persist in later puberty (Kerr and Knell, 1988;Ariyaratne and Chamindrani Mendis-Handagama, 2000;Ivell et al, 2003).…”
Section: Effect Of (Bu) 2 Camp and Paracrine Factors On Pflc Prolifermentioning
confidence: 99%
“…differentiation into adult Leydig cells in neonatal prepubertal rats [4,5]. In addition, daily injections of T3 to neonatal prepubertal rats accelerates the differentiation of Leydig cells [5].…”
mentioning
confidence: 97%
“…These changes were caused by a prolongation of Sertoli cell proliferation and a delay in Sertoli cell differentiation (9,18,42,52). At the same time, under these hypothyroid conditions, progenitor-type Leydig cell formation was reported to be arrested up to 21 days after birth in rats (27). Following cessation of the hypothyroid condition at the age of 26 days, developing adult-type Leydig cells started to proliferate massively (Teerds KJ, unpublished data), leading to an approximate 70% increase in the Leydig cell population in adulthood (14,46).…”
mentioning
confidence: 98%